THE POETICAL ACTUALIZATION OF TERMS IN THE LITERARY WORKS (as the sample of the works of Askad Mukhtar, Abdullah Kahhor and Ulmas Umarbekov) - JAMOLIDDINOVA, Dilnoza (International Journal of Psychosocial Rehabilitation, 2020)
-In the article the terms are scientifically proved that they are also the unit of expression. The lingvopoetic peculiarities of the terminology used in the works of Uzbek writers are studied. Poetic actualization of the terms is illustrated with the examples taken from the literary works.